Entre a casa e a rua: uma história da mocidade de Diamantina-MG no final do século XIX - Helder de Moraes Pinto (2015)
The present research aimed at comprehending the social practices of youth educational process that occurred in the city of Diamantina, in the state of Minas Gerais, Brazil, by the end of the 19th century. We intended specially to understand the daily practices of youth in home environment, that is, the living together at home and in a few public spaces. The characters studied were specially the chidren of local elite, but not only them. We sought to analyze the relationship of the youth with different rites of familiar tradition, that is, the uses and habits related to the way to occupy the home environment, as well as the ways of processing the feeding gatherings; ordinary ceremonies where the young were thrown and intertwined in a system of ideas, values and hereditary gestures. We considered the notion of daily live as a time-space dimension where the young processed a given social, moral, aesthetical and ethical education. Initially, we considered education the process through which certain social practices occurred repeatedly becoming habitual exercises, many of which naturalized by the group of relatives and friends. The relationship with such uses and habits demanded that the young developed certain capabilities for planning and performing such movements and operations of assimilation, resistance, exchange and creation, this because, in many cases, they wanted to maintain favorable positions in face of the problems? We have used as sources for investigation the autobiographical literature of people born in Diamantina, in the second half of the 19th century; newspapers circulating on the city at this same age; a few notary, photographic and engraving documents, among others. The study allowed us to conclude that some young were resistant to given uses and habits, but not the point of stopping practicing them. In many cases, they complained with themselves for accepting a given traditional situation. In other events, they confronted objectively the adult generations, exposing their points of view about matters? They made usage of those habits and use, often, as a form of deriving some pleasure of advantage. They insisted in being close to the adults, for it was a way for them to be acquitted of most serious polemics through which the communities they belonged passed. However it was not uncommon for them to make up a reason to get away of the home environment, and enjoy the adventures and risks offered by the street and all it could afford. In the street, the celebrations of popular saints undertaken by the religious sisterhoods offered different spaces where the young sought their interests, even those that were contrary to the public order established by official Catholicism. However, in ordinary days, it was always possible to enjoy bohemia in several points of the city; uninterruptedly some girl or boy programmed a meeting for the guests to enjoy and speak. These gathering, strongly articulated by relative and friendship bound, were marked continuously by reflections on literature, power, politics, moral, question, attaing to Diamantina. A few of these groups of young were also dedicated to write about critical questions of the time, such as the blemishes of school regime, the lack of civil and political rights of the feminine gender, given rise to a small pamphleteer writting, printed and distributed by them in that and in other towns. Basically, those young sought to dialogue between themselves and with the society surrounding them, aiming at exposing which were their impressions and expectations concerning the experiences of the end of that century; and, by doing so, they ended up projecting future images charged with perspectives of historical ruptures.